PERENCANAAN PEMBANGUNAN BIDANG KETAHANAN PANGAN DI KABUPATEN PASURUAN - Luluk Khuroidah, Mrs. (Jurnal Ilmiah Administrasi Publik, 2012)
The research described and analyzed the areas of food security planning in Kabupaten Pasuruan. The research used a descriptive method and qualitative approach. Data sources were derived from informants and documents. The data collecting technique used interview and documentations. Data were analyzed using an interactive model. The results of this study were the field of food security development planning in Kabupaten Pasuruan shows that it is dominated by a top down approach. Planning mechanisms through forums musrenbang and technocratic had generally been in accordance with the planning cycle of Conyers and Hills. Kelompok Tani Nelayan Andalan (KTNA) was less involved in planning where many of their proposals were proposed through agricultural extension workers (PPL). so"es +Pe:JA;mso-bidi-language:HE>The result of this research could be used as an insight to develop a new system more effective and efficient in the future. This research also presents some suggestions for short, middle, and long-term planning for Kudus Local Government in developing e-government in the future, to shape the good governance for public service. `vga+P>secondly to analyze the utilization of the IP4Tâs results in the land management planning process in East Java.Â  This research used qualitative method with descriptive approach. The conclusions obtained, Execution / implementation of IP4T in East Java Province, has been running well in quantity has been largely imposed to meet the target over the years, but planning activity from the activity IP4T land in East Java Province, it can be said the less successful as a result of these activities IP4T less fully utilized